Adaptation of social class in Indonesian translation of the Great Gatsby by Maria Lubis - Shazfa Qatrin Aisha; Permanaludin, Udayani; Pramita, Agry (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study examines how elements of social class are adapted in Maria Lubis’s Indonesian translation of F. Scott Fitzgerald’s The Great Gatsby. The primary aim is to analyze the portrayal and transformation of social class indicators from the source text into the target language, focusing on selected characters and key events. Employing a qualitative approach with a descriptive analytical method, the research identifies narrative components that reflect class distinctions and explores the translator’s strategies in rendering these into Indonesian. The analysis draws on Peter Newmark’s theory of adaptation and Max Weber’s conceptualization of social class, which distinguishes between class, status, and power. Newmark’s adaptation technique, which involves modifying culturally specific elements for target readers, is employed to reveal how social critiques embedded in the original text are made accessible to an Indonesian audience. The findings indicate that the translation succeeds in preserving core aspects of class stratification while conveying the novel’s critique of the moral decay underlying material wealth. Notably, the translation underscores the disconnect between economic status and ethical integrity, exemplified by the contrast between Gatsby and the upper-class elite. Despite the translator’s effective role as a cultural mediator, some nuances inevitably remain lost in translation due to cultural and linguistic differences.